The Application of Apple (Malus sylvestris) Extract-Based Gel: Effects on Teeth Colour Change and Hardness - Fitri, Atika Resti; Limraksasin, Phoonsuk; Yendriwati; Siregar, Nindira Yasmine; Filia Dana (TALENTA, 2024)
Manalagi apple extract, which contains malic acid, has the potential to be used as an alternative teeth whitening. Therefore, this study aimed to investigate the effect of Manalagi Apple (Malus sylvestris) extract-based gel on teeth colour change and hardness. It included an experimental laboratory with a pre-test, post-test, and control group design. The samples consisted of thirty anterior extracted teeth which were divided into five groups, including negative control, 10% carbamide peroxide, 25%, 50%, and 75% extract. Teeth were discoloured for seven days using a coffee solution, and gel was applied for 8 hours a day for 14 days. Teeth colour change was assessed using colourimeter device, while hardness was measured using a micro Vicker hardness tester. The data analysis was carried out using the Kruskal-Wallis test followed by Mann Whitney test, and the t-dependent test. The result showed that there was a significant change in teeth colour after treatment with 75% apple extract gel compared to the negative control and carbamide peroxide 10%. The extracted gel significantly increased teeth hardness value. These results showed that apple extract-based gel improves teeth colour without negatively affecting the hardness, suggesting that apple extract-based gel can potentially be used as a dental whitening agent.